Proceedings of the 1st International Conference on Innovation in Education (ICoIE 2018) 2019
DOI: 10.2991/icoie-18.2019.130
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Teacher Dispatching Program For Indonesian Children’s Education In Sabah Malaysia

Abstract: The purpose of this study is to evaluate the teacher dispatching program for Indonesian children's education in Malaysia. Currently, there are 53,687 children of Indonesian citizens in Malaysian Sabah plantations that have difficult access to education. Since 2006, the government of Indonesia has periodically sent teachers to provide education services for Indonesian children in Sabah Malaysia. This research uses the qualitative approach with the evaluative method. The research model used is a model developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In this study, evaluation was performed using Stufflebeam's Context-Input-Process-Product (CIPP) model, which is a curriculum evaluation model. The CIPP model was preferred since it is one of the most effective models for evaluating different types of programs (Kim Anh, 2017;Lee Abdullah & Wei, 2017;Jamil & Mukhadis, 2017;Mayo & De Balazs, 2013;Suspalupi et al, 2018;Yurdakul et al, 2014). The fundamental concepts of the CIPP model are context, input, process, and product evaluation, as in its acronym.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, evaluation was performed using Stufflebeam's Context-Input-Process-Product (CIPP) model, which is a curriculum evaluation model. The CIPP model was preferred since it is one of the most effective models for evaluating different types of programs (Kim Anh, 2017;Lee Abdullah & Wei, 2017;Jamil & Mukhadis, 2017;Mayo & De Balazs, 2013;Suspalupi et al, 2018;Yurdakul et al, 2014). The fundamental concepts of the CIPP model are context, input, process, and product evaluation, as in its acronym.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions affect the effectiveness of the teaching and learning process [17]. Even though the teacher dispatch program has been carried out, improvements are still needed [18]. Other studies have also found that the management of Indonesian primary school and CLC teachers in Malaysia is still substandard and not systematic [19].…”
Section: Introductionmentioning
confidence: 99%